SAMHD1's protein expression profile in humans - Schmidt, Sarah; Schenková, Kristína; Adam, Tarek; Erikson, Elina; Lehmann-Koch, Judith; Sertel, Serkan; Verhasselt, Bruno; Fackler, Oliver Till; Lasitschka, Felix; Keppler, Oliver Till (Journal of leukocyte biology, 2015)
First cross-sectional expression profile of SAMHD1 in human tissue provides insight into its regulation on HIV target cells and effects its expression or phosphorylation state by proinflammatory cytokines.
Gesehen am 02.07.2020